2013
DOI: 10.1039/c3cc40432c
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic anticancer complexes of lapachol: metal centre-dependent formation of reactive oxygen species and correlation with cytotoxicity

Abstract: Organometallic Ru(II), Os(II) and Rh(III) complexes of lapachol induce apoptosis in human tumour cell lines in the low μM range by a mode of action involving oxidative stress, especially in the case of the ruthenium compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 17 publications
0
99
1
2
Order By: Relevance
“…The isobidentate nature of the OsO 2 C 2 moiety is evidence of delocalization of the C O bonds of the tropolone ligand upon coordination [C11-O1 = 1.303 (11), C17-O2 = 1.299 (11)Å ]. The aromatic ring of the p-cymene ligand appears almost planar, with the displacement of the arene ring centroid from the Os II center [1.676 Å ] being comparable with other similar complexes (Peacock et al, 2007;Kandioller et al 2013).…”
Section: Structural Commentarymentioning
confidence: 51%
See 1 more Smart Citation
“…The isobidentate nature of the OsO 2 C 2 moiety is evidence of delocalization of the C O bonds of the tropolone ligand upon coordination [C11-O1 = 1.303 (11), C17-O2 = 1.299 (11)Å ]. The aromatic ring of the p-cymene ligand appears almost planar, with the displacement of the arene ring centroid from the Os II center [1.676 Å ] being comparable with other similar complexes (Peacock et al, 2007;Kandioller et al 2013).…”
Section: Structural Commentarymentioning
confidence: 51%
“…Only one orientation of the disordered benzene ring is shown. Kandioller et al, 2013) have been reported.…”
Section: Figurementioning
confidence: 99%
“…The aromatic C\H hydrogen atoms were positioned stereochemically and were refined with fixed individual displacement parameters [U iso (H) = 1.2 U eq (Csp 2 )] using a riding model with an aromatic, C\H bond length fixed at 0.93 Å. Methylene groups of the dppb ligand in the complex (5), and methine group of the lapachol were set as isotropic with a thermal parameter 20% greater than the equivalent isotropic displacement parameter of the atom to which each one was bonded, whereas methyl groups were set with U iso (H) values of 1.5U eq (C methyl ). Tables were generated by WinGX [25] and the structure representations by ORTEP-3 [18] and MERCURY [21]. The main crystal data collections and structure refinement parameters for (1) and (5) are summarized in Table 1.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…In fact, there are some findings showing that lapachol-metal complexes are biologically more active than the free molecule [15][16][17][18]. Ruthenium complexes are considered to be one of the most promising types of metal compounds for cancer treating, due its interesting chemical properties, such as: versatility in ligand exchange, octahedral geometry and variability of oxidation states [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation